Unexpected Favorable Outcome to PD-1 Antibody Plus Lenvatinib in a Patient With Recurrent Intestinal Follicular Dendritic Cell Sarcoma: A Case Report and Literature Review - Lei, Yanna; Zhao, Sha; Jiang, Ming (Frontiers in Immunology, 2021)
Background Follicular dendritic cell sarcoma (FDCS) is an uncommon malignant cancer, and there is no standard treatment to date. Resection followed by adjuvant chemotherapy or radiation is considered the most commonly used strategy for treatment. However, the treatment for patients who have progressed after systemic treatment is more controversial. Case summary In this case report, we describe a 57-year-old man with primary small intestine FDCS where surgery and second-line systemic chemotherapy failed. After disease progression (PD), the patient received sintilimab plus lenvatinib as third-line treatment and achieved a progression-free survival (PFS) with 7 months. Conclusion This is the first report of a FDCS patient treated with immune checkpoint inhibitors (ICIs) and antiangiogenic agents, sintilimab and lenvatinib, as third-line therapy. Our case provides a potential therapeutic option for patients with FDCS who progressed after multiline therapy.